The effects of endogenous melatonin on brain tissue oxidative stress induced by photoperiodic alterations and iron overloading in rats - Hernando, Marcelo Pablo (2024)
Melatonin is a potent endogenously occurring antioxidant with the pleiotropic activities to neurodegenerative diseases associated with brain oxidative damage. In this study, we examined the prolonged photoperiodic alterations and iron (Fe) overload on melatonin production and brain oxidative stress in rats. The result showed that the 15 days of constant light (CL) exposure did not low the melatonin production but the 15 days of constant darkness (CD) significantly increased serum melatonin level in rats. The Fe treatment in both CL and CD conditions significantly reduced endogenous melatonin levels and increased brain tissue lipid peroxidation. Fe as a toxic transition metal can induce Fenton reaction to generated hydroxyl radical which can damage the neuronal cell membrane and impair the brain antioxidant system. In the current study, we observed the imbalanced antioxidant defense alterations upon Fe treatment in rat brain including the increased levels of alpha-tocopherol (α-T) and total thiols and the reduced melatonin level and catalase (CAT) activity. We speculated that the reduced melatonin level caused by Fe was due to its consumption since melatonin served as a metal chelator and antioxidant. Understanding these aspects enhances knowledge of brain Fe metabolism and its role in neurodegenerative disorders as well as the potential protective effects of melatonin on this metal.